Adaptive morpho-anatomical traits of Euphorbia yaroslavii populations in the Zailiysky Alatau, Kazakhstan - ZHANSAYA TURGARA; ABIBULLA AMETOV; AKERKE KENESBAY; ELMIRA IMАNOVA; GULNAZ SYPABEKKYZY; BEKTEMIR OSMONALI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Turgara Z, Ametov A, Kenesbay A, Imanova E, Sypabekkyzy G, Osmonali B. 2026. Adaptive morpho-anatomical traits of Euphorbia yaroslavii populations in the Zailiysky Alatau, Kazakhstan. Biodiversitas 27 (6): d270604. https://doi.org/10.13057/biodiv/d270604. Euphorbia yaroslavii is a narrow-range endemic of the northern Tien Shan, restricted to foothill steppe and clayey habitats of the Zailiysky Alatau, Kazakhstan and is insufficiently studied in terms of morphological and anatomical variability. This study aimed to evaluate interpopulation variation in morphological, anatomical, and seed micromorphological traits of E. yaroslavii under contrasting ecological conditions. Three spatially isolated populations were analyzed using a comparative approach that included morphometric measurements of vegetative and generative organs, anatomical investigation of leaf, stem, and root structures, and scanning electron microscopy of seed surfaces. The results showed pronounced interpopulation differentiation mainly in vegetative morphology and anatomical structure. The greatest variability was recorded in leaf thickness, mesophyll organization, and development of conductive tissues, reflecting habitat-related environmental differences. In contrast, generative traits, including cyathium and seed dimensions, were relatively stable. ANOVA confirmed significant differences (p<0.05) in most vegetative and anatomical parameters, whereas reproductive traits showed no significant differences. Correlation analysis revealed coordinated variation among structural traits of different organs. Population differentiation in E. yaroslavii is primarily expressed in vegetative and anatomical features, while reproductive traits remain stable. These findings provide a quantitative framework for understanding adaptive variation and support population-based conservation strategies for this endemic species.